International trade, development traps, and the core-periphery structure of income inequality - Dominik Hartmann; Mayra Bezerra; Beatrice Lodolo; Flávio L. Pinheiro (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2019)
Research on economic complexity has shown that a country's type of exports conditions its future path of economic diversification and economic growth. Yet little emphasis has been put on the inequality associated with the types of products traded between countries and different regions of the world. Here we analyze the income inequality associated with the imports and exports of 116 countries in the period from 1970 to 2010. Our analysis shows that methods from network science and visual complexity research can help to reevaluate old theories in economics, such as coreperiphery structures in international trade or structural development traps. Our results illustrate that the core-periphery structure of global trade affects not only the income inequality between countries, but also the income inequality within countries. Moreover, they reveal the structural constraints that developing and emerging economies face in promoting inclusive growth and benchmark their productive transformations with cases of successful catching up and developed economies. The results show that countries, such as South Korea or Germany, have benefited from outsourcing high inequality products. In contrast, some middle-income countries, such as Brazil or South Africa, face structural development constraints consisting of a large average distance of their export products to low inequality products and a "gravitational force" towards high inequality products. Finally, developing economies, such as Nicaragua or Sri Lanka face a double development trap for inclusive growth, as their economies depend on both a large share of high inequality exports and imports.
urn:nbn:de:bsz:100-opus-15781
Keywords: 330; trade; inequality; economic complexity; development trap